Course Book Berbasis Android - Dwianto, Fitra; Fujiyanti, Linda; Mubaroh, Sari (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
UPTD SDN13 has a problem of not having new books with the latest content available. Most of the library's collection contains outdated content. This problem needs to be addressed immediately, as information that is no longer relevant changes over time and years of research, and such information is generally available for free on the Internet. Therefore, it is possible to develop an application that collects such data and provides access to it. This research aims to increase the interest of SDN13 students in reading study materials and to facilitate their access to the latest materials. The development methodology adopted in this study is agile methodology and application testing is carried out using UAT (User Acceptance Testing) approach and white box testing methodology. As a result of UAT (User Acceptance Testing) testing, the score obtained by teachers was 85.66% and the 6th grade students obtained 94.13%. Therefore, the UAT results show that this application meets the criteria of being